Corrosion behavior of austenitic and ferritic steels in alkaline and water-salt solutions - Kniazieva, Hanna; Kniaziev, Sergey; Tomashevskyi, Roman; Kanunnikova, Nadia; Vorobiov, Bohdan; Shestopalov, Oleksii; Sakun, Antonina (Physics and Chemistry of Solid State, 2024)
The paper presents the results of studies of the corrosion behavior of austenitic and ferritic steels in alkaline, sulfide, and chloride environments. Structural changes on the surface when the steels are kept in solutions at room temperature are shown. The chemical composition of the steels was determined, and the exact phase-structural composition was theoretically predicted and metallographically determined. It was found that austenitic steel is almost not subject to sulfide corrosion at room temperature and chlorine-containing substances. At the same time, ferritic steel, under the same conditions, has significant corrosion damage on the surface, especially in places of mechanical damage.